EDUCATION AND CULTURAL VALUES: COMPARISON BETWEEN INDONESIA, AUSTRALIA, USA AND JAPAN - Nadyya Nulhusni; Firman; Riska Ahmad (Yayasan Citra Dharma Cindekia, 2021)
This article discusses education and cultural values: comparisons between Indonesia, Australia, usa and Japan using references from relevant literature studies. Education is a human process to make humans have a sense of humanity, become adults, and fully human beings in order to be able to carry out their basic duties and functions fully and develop culture. Culture and education have reciprocal relationships because culture can be preserved and developed by passing on culture from generation to generation to the next by way of education.